Differentiation of distinct mesoderm subtypes from regulatory interactions between FGF and BMP signaling - Gattiglio, Marina (Technische Universität Dortmund, 2022)
Distinct mesodermal precursors arise during gastrulation in a precise temporal and spatial manner. In the mouse, the cells differentiating earlier in a more proximal position form the precursors for the heart and vasculature, followed in a more distal position by precursors of the urogenital system and then the musculoskeletal system. Mesoderm patterning is controlled by signals such as BMP4, produced by the extraembryonic ectoderm, and FGFs and WNTs produced by the epiblast itself. How do these signals interact in this process and whether cell-cell crosstalk can influence mesoderm patterning is still largely unknown. Here I address this question with a 2D cell culture model that employs primed pluripotent stem cells resembling mouse epiblast cells and differentiates them with precise concentrations of different signaling molecules in a chemically defined medium. By titrating BMP4, I observe that high concentrations of BMP4 promote the expression of proximal mesoderm markers, while intermediate to low concentrations favour distal and pan-mesoderm markers. The opposite effect is seen with a titration of FGF. A scRNAseq analysis revealed that endogenous FGF signaling lead to the differentiation of heterogeneous mixtures of cell types, and that their proportions were affected by the dose of exogenous FGF. Furthermore, higher doses of exogenous FGF reduced the expression of BMP ligands in the cells, and promoted the expression of selected WNT ligands and endogenous FGFs, indicating the existence of a positive FGF feedback loop. Cells associated with high FGF signaling levels were also found to be spatially clustered in the cultures, suggesting that this loop could generate coherent clusters of cells with discrete identities in a cell population. Based on these findings, I propose a molecular mechanism for the FGF feedback loop. Together, these results indicate that the patterning of the mesoderm is dependent on a combination of external signaling and cell-cell crosstalk.

Während der Gastrulation entstehen distinkte mesodermale Vorläuferzellen in einer präzisen zeitlichen und räumlichen Abfolge. In der Maus bilden Zellen, die früh aus proximalen Positionen differenzieren, die Vorläufer von Herz und Gefäßsystem, während später aus distalen Positionen Vorläufer des urogenitalen Systems und anschließend des Bewegungsapparats gebildet werden. Die Identität mesodermaler Zellen wird durch Signale wie BMP4, die vom extraembryonalen Ektoderm produziert werden, sowie von FGFs und WNTs, die vom Epiblast selbst produziert werden, kontrolliert. Wie diese Signale interagieren und ob Zell-Zell-Kommunikation die Mesodermbildung beeinflusst, ist größtenteils unbekannt. Um diese Frage zu beantworten verwende ich ein 2D-Zellkulturmodell aus epiblastartigen Mausstammzellen, die mit verschiedenen Konzentrationen bestimmter Signalmoleküle in einem chemisch definierten Medium differenziert werden. BMP4-Titrierung zeigte, dass hohe Konzentrationen von BMP4 die Expression proximaler Mesodermmarker unterstützen, während mittlere bis geringe Konzentrationen distale und panmesodermale Marker begünstigen. Das Gegenteil wird durch FGF-Titrierung ersichtlich. Die Analyse von scRNAseq-Daten zeigte, dass endogene FGF-Signale zur Differenzierung heterogener Zelltypen führen, deren Verhältnis von der Dosis von exogenem FGF abhängt. Zudem reduzierten höhere Dosen exogenen FGFs die Expression von BMP-Liganden in den Zellen und unterstützten die Expression einiger bestimmter WNT-Liganden und endogenen FGFs, was die Existenz eines positiven FGF-Feedback-Loops impliziert. Zellen, die mit einem hohen FGF-Signal-Level assoziiert sind, waren außerdem innerhalb der Kultur räumlich geclustert, was die Vermutung nahelegt, dass der FGF-Feedback-Loop kohärente Zellcluster mit diskreten Identitäten innerhalb einer Zellpopulation generiert. Basierend auf diesen Erkenntnissen schlage ich einen molekularen Mechanismus für den FGF-Feedback-Loop vor. Zusammengenommen zeigen diese Ergebnisse, dass die mesodermale Identität in Abhängigkeit einer Kombination von externen Signalen und Zell-Zell-Kommunikation bestimmt wird.
Keywords: EpiSCs; Mesoderm differentiation; scRNAseq; 570; 540; Gastrulation; Maus